2012
DOI: 10.1111/sjop.12002
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking infants: Investigating the role of attention during learning on recognition memory

Abstract: In the present study, eye tracker methodology was used to explore whether there were age-related changes in the focus of infant attention during a learning event and subsequent recognition memory for event features. Six-and 9-month old infants watched a video of an adult demonstrating a sequence of actions with an object while visual attention was recorded using an eye tracker. At both ages, attention was focused primarily on the object and person, with the background attended to for approximately 12% of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 37 publications
(68 reference statements)
7
25
1
Order By: Relevance
“…This result is noteworthy as previous studies either focused solely on the level of mean values or used experimental paradigms that did not incorporate an eye-tracking technique; a congruency on the mean level between attention allocation and subsequent recall of webpage content has been previously reported for animated versus non-animated banner ads on webpages (Hamborg et al, 2012) as well as for personalized versus non-personalized banner ads (Köster, Rüth, Hamborg, & Kaspar, 2014). Some researchers did not find a link between attention and memory (Taylor & Herbert, 2013;Xing & Isaacowitz, 2006). Moreover, some studies investigated attention memory for emotional stimuli in distinct experiments, making correlational analyses impossible (e.g., Fung, Isaacowitz, Lu, & Li, 2010).…”
Section: Discussionsupporting
confidence: 49%
“…This result is noteworthy as previous studies either focused solely on the level of mean values or used experimental paradigms that did not incorporate an eye-tracking technique; a congruency on the mean level between attention allocation and subsequent recall of webpage content has been previously reported for animated versus non-animated banner ads on webpages (Hamborg et al, 2012) as well as for personalized versus non-personalized banner ads (Köster, Rüth, Hamborg, & Kaspar, 2014). Some researchers did not find a link between attention and memory (Taylor & Herbert, 2013;Xing & Isaacowitz, 2006). Moreover, some studies investigated attention memory for emotional stimuli in distinct experiments, making correlational analyses impossible (e.g., Fung, Isaacowitz, Lu, & Li, 2010).…”
Section: Discussionsupporting
confidence: 49%
“…When 3- (Bronson, 1991) and 5-month-old infants (Jankowski, Rose, & Feldman, 2001) are familiarized with a static picture, visual recognition for that stimulus is related to short, distributed looking behavior. In contrast, using a video of the well-established puppet imitation task (see also Barr et al, 1996; Barr, Muentener, & Garcia, 2007), Taylor and Herbert (2013) found limited evidence for a relationship between attention during learning, measured using an eye tracker, and visual recognition memory at 6 and 9 months of age. Although imitation studies using the puppet task traditionally involve the experimenter using empty language cues to direct infant’s attention to the target event, the video demonstration in this study was silent, to be consistent with previous eye tracking studies (e.g., Vivanti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, given that 9-month-old infants are on the cusp of showing increased flexibility in their memory abilities, with considerable individual differences being observed at this age (e.g., Herbert et al, 2006), it is important to assess memory performance when abilities are more robust, later during infancy, or even in adulthood. Second, the only measure of memory obtained by Taylor and Herbert (2013) was infants’ visual recognition for the components of the demonstration video. Prior research has shown that 6-month-old infants may fail to show recognition memory for the puppet following a live demonstration, even though they still exhibit behavioral recall for the target actions that were performed with it (Gross, Hayne, Herbert, & Sowerby, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations